Young adults training: experience of intervention-lessons with students of Psychology from the University "Sapienza" of Rome. - Masina, Emilio; Grasso, Paola; Russo, Maria Rosaria; Russo, Sonia (Rivista di Psicologia Clinica, 2013)
The papers presents a training experience regarding young adult-students enrolled in the third year of the Faculty of Psychology, the Laboratory on youth uneasiness, which is proposed in order to overcome a traditional lesson model and integrate theory, practice and students’ personal involvement. The "classroom setting”, i.e. the relationship between teachers, staff and students in their respective functions, was planned and handled by the trainers of the laboratory as if it were "a clinical case", that is a client to be developed. There were two main goals: 1) Facilitate the detection of a psychological function in the interventions addressed to adolescents and their ecosystems of reference that could express in different work contexts and integrate theoretical and emotional aspects; 2) Promote the subjectivation of the young participants favoring their transition from late adolescence to adulthood. Through the use of tools such as report and role-playing the authors dealt with the “here and now” of the relationship of the group in the classroom in the present training to track and elaborate the dimensions of the students’ "past training" based on an individualistic stereotype, that is on the individual as a stereotypic entity, cut off from its cultural context and relational. This elaboration has made it possible to facilitate the integration of aspects who were split by students: on one hand, adolescence as a way of being in a context and phase characterized by bodily and psychological changes; on the other hand, the model of analysis of demand, learned in the degree course, mythologized and therefore inapplicable, with specific organizational contexts in which the same model can be used.